THE DETERMINANT FACTORS IN PERFORMANCE OF PRIVATE HIGHER EDUCATION IN GUANGDONG PROVINCE CHINA - Ma Zhiguang; Shakirah Noor Azlan, (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME'S (AIJBES), 2025)
As the world economy and society have undergone rapid structural changes, colleges have been faced with a new set of crises and challenges. Among those are not only the challenges of structural knowledge changes but also those of management changes. This study is mainly research on the determinant factors of performance of private higher education in Guangdong province China. In addition, in this research mainly focus on the private higher education institutions (PHEI)in Guangdong Province, China, as Guangdong offers 67 undergraduate colleges and universities (including PHEIs), 87 specialized colleges and universities, and 14 adult colleges and universities as of June 30, 2020.The number of staff at China's colleges and universities was around 177,900 in 2020. Hence, in this research target adopt quantitative method by using questionnaire to collect 750 respondents to examine the relationship of independence variables such as knowledge management, leadership and organizational culture towards dependence variable of corporate performance of PHEIs while mediation role of innovation. All data collected to test hypotheses using the statistical technique SmartPls 4.0. This study will enrich the theoretical research on the heterogeneity of the senior management team of Chinese higher education groups and performance in Guangdong Province.